The Impact of Discovery Learning Model Assisted of Mind Mapping Media Based on Zooming Presentation on Understanding of Students' Concepts in Dynamic Electricity Materials - Kholida, S. Ida; Qori'ah, Fasihatul; Suprianto, Suprianto; Sunarti, Titin (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2022)
In the teaching process needed by the teacher, namely the use of learning models, because it creates an atmosphere of effectiveness in the classroom and also for understanding and mastering concepts in physics material. According to MA Miftahul Ulum Bettet, students' conceptual understanding, especially in physics, is low, the evidence is that students' daily test results do not reach the minimum completeness criteria. The purpose of this study is whether there is a significant effect applying discovery learning as a learning model with the help of mind mapping based zooming presentation media on dynamic electrical material on understanding concepts. This type of research is a quasi-experimental using a pretest posttest control group design. All students of MA Miftahul Bettet are the research population, while 2 classes as samples are taken randomly, namely class XIA and class XIB. The data acquisition technique uses a test instrument. The data was processed using t-test, the value of tcount > ttable (7.526>2.606) so significant (2-tailed) <0.05 (0.000 <0.05). For this reason, the conclusion of this study is that there is an effect of the application of the discovery learning model with the help of mind mapping based zooming presentation media on students' understanding of the concept of dynamic electricity.